Computing Topological Indices of Some Types of Benzenoid Systems and Nanostars - YOUSEFI-AZARI, H.; ASHRAFI, A.R.; BAHRAMI, A.; YAZDANI, J. (Asian Journal of Chemistry, 2010)
The PI and Szeged are two of most important topological indices defined in chemistry. In this paper, we compute the PI and Szeged indices of some important classes of benzenoid systems and nanostars. Some open questions are also included in the paper.